NEUROLEPTIC MALIGNANT SYNDROME IN AN ELDERLY PERSON WITH A HISTORY OF ATYPICAL ANTIPSYCHOTIC TREATMENT AND COMORBIDITIES: A CASE REPORT - Fahira, Aulia; Setyanagara, Adwin; Ulya, Zuhrotun (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction: Neuroleptic Malignant Syndrome (NMS), a neuropsychiatric emergency, can develop in patients with antipsychotic medications. This is a matter of concern due to the high frequency of psychotic diseases in Indonesia, affecting an estimated 2.6 million people. This paper will examine a case of NMS who exhibited various risk factors and clinical manifestations, which happened in Kediri, a city in Indonesia that lacks of dedicated mental hospital or intensive care unit for mental health. Method: In this paper, we reveal about a case report about a 63-year-old man presented to the emergency room with abrupt onset of fever and cognitive impairment. He took olanzapine and clozapine for schizophrenia, which was not often treated. The patient had gait disturbances, pronounced tremors, rigidity, and autonomous movement of the mouth. Examination results were blood pressure of 88/55 mmHg, pulse 123x/minute, respiratory rate 24x/minute, body temperature 42°C. Supporting investigation results showed leukocytosis, hypokalemia, pneumonia and cardiomegaly. Initial management included discontinuation of neuroleptic drugs, administration of oxygen, rehydration, and symptomatic medications. Results: This is a rare case of NMS in geriatric patient happened in a rural area, Kediri, a small city in Indonesia which experiences higher temperatures in comparison to other cities. This case is quite complex due to the treatment options, a history of poor drug compliance, elderly conditions and comorbidities. Discuss: For both confirmed and suspected instances of NMS, basic treatment suggestions include stopping antipsychotic medication, continuously monitoring vital signs, minimizing extremes in temperature, introducing fluids, correcting electrolyte imbalances, and providing other supportive measures as needed Conclusion: NMS should be closely monitored in psychosis patients with a history of noncompliant medication use and concomitant conditions. To save lives, prompt and adequate medical attention is essential.